Three primary testicular tumours: Trials and tribulations of testicular preservation - Forbes, Connor M; Metcalfe, Charles; Murray, Nevin; Black, Peter C (Canadian Urological Association Journal, 2013)
Balancing recurrence risk, side effects and patient preference in the treatment of multiple metachronous testicular tumours can be challenging. We present the case of a young male patient who developed 3 different primary testicular neoplasms over an 8-year period, each associated with retroperitoneal lymphadenopathy requiring chemotherapy. The first tumour at age 19 was managed with radical orchiectomy. Four years later, a partial orchiectomy was performed to remove 2 small lesions. Another 4 years later, a complete orchiectomy was required for an additional tumour. This case highlights the caveats of testis-sparing surgery for testis cancer and the need for careful surveillance in these patients.